BABAD GIRI KEDHATON: KAJIAN STRUKTUR TEKS - Mudlofar (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This study aimed to describe the structure of the manuscript Babad Giri Kedhaton (BGK). This research uses descriptive method, with objective approach. Based on the analysis, the findings were as the following: Structure elements contained in the text BGK can be stated as follows. BGK theme was reflected in the characterizations. BGK characterizations was in support of the theme. Characters in the text were divided into two, namely the central character and the supporting characters. The central character was Kanjeng Ainul Yaqin Sunan (Sunan Giri), while the supporting character was Maulana Awwalul Islam, Sunan Ampel, Nyahi Gedhe Pinatih, Belambangan King and his daughter, Kanjeng Dalem Sunan, and Sunan Prapen. Seventh characters were bound genealogically. Presentation of the story in BGK text was using the forward plot. It could be seen through the interwoven stories stringed with the words: mangka, nuli, lajeng, peputra, apeputra, kocapa, and punika. Background or scene of the story is realistic, it can be seen geographically. Background stories focused on Kedhaton Giri, a place that was on the top of Mount Giri, which is located in Gresik now. That was where Kanjeng Sunan Giri (King Satmata) established the kingdom under the name Giri Kedhaton.